The Common Effects of Sleep Deprivation on Human Long-Term Memory and Cognitive Control Processes - Kim, Taehyun; Kim, Sejin; Kang, Joonyoung; Kwon, Minjae; Lee, Sue-Hyun (Frontiers in Neuroscience, 2022)
Sleep deprivation is known to have adverse effects on various cognitive abilities. In particular, a lack of sleep has been reported to disrupt memory consolidation and cognitive control functions. Here, focusing on long-term memory and cognitive control processes, we review the consistency and reliability of the results of previous studies of sleep deprivation effects on behavioral performance with variations in the types of stimuli and tasks. Moreover, we examine neural response changes related to these behavioral changes induced by sleep deprivation based on human fMRI studies to determine the brain regions in which neural responses increase or decrease as a consequence of sleep deprivation. Additionally, we discuss about the possibility that light as an environmentally influential factor affects our sleep cycles and related cognitive processes.